ANALISIS PENINGKATAN AKSESIBILITAS PELAYANAN PUBLIK BAGI PENYANDANG DISABILITAS DI INDONESIA - Syaza Chairunnisa; Eko Budi Sulistio (Dialogue : Jurnal Ilmu Administrasi Publik, 2025)
This study aims to analyze the improvement of accessibility and public services for people with disabilities in Indonesia, focusing on policies and their implementation across various public sectors. People with disabilities often face barriers in accessing adequate public services, necessitating a more inclusive and responsive approach to meet their needs. The research employs a qualitative method with a descriptive approach, utilizing literature review techniques to examine relevant literature and policies. Secondary data is collected from journals, books, and official government documents that discuss accessibility and public services for people with disabilities. The findings indicate that, despite efforts to improve accessibility through the enactment of Government Regulation (PP) No. 70 of 2019 and Law No. 8 of 2016, the implementation of these policies in the field still faces several challenges, such as inadequate infrastructure and a lack of public awareness. The study concludes that stronger synergy between the government, private institutions, and society is needed to ensure the rights of people with disabilities to access public services are fully realized.